2021
DOI: 10.1021/acsnano.1c00156
|View full text |Cite
|
Sign up to set email alerts
|

Förster Resonance Energy Transfer Nanoplatform Based on Recognition-Induced Fusion/Fission of DNA Mixed Micelles for Nucleic Acid Sensing

Abstract: The dynamic nature of micellar nanostructures is employed to form a self-assembled Forster resonance energy transfer (FRET) nanoplatform for enhanced sensing of DNA. The platform consists of lipid oligonucleotide FRET probes incorporated into micellar scaffolds, where single recognition events result in fusion and fission of DNA mixed micelles, triggering the fluorescence response of multiple rather than a single FRET pair. In comparison to conventional FRET substrates where a single donor interacts with a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Therefore, OA is one of the excellent and efficient candidates for regulating excited-state luminescence. [41][42][43][44] Here, we successfully regulated the luminescence of a series of difluoroboron β-diketonate (DFBK) chromophores that were emitted from different electronically excited states at the interface of oleic acid molecules. Selective excitation of OA in the OA-DFBK composites led to blue luminescence, which could be attributed to the locally excited state emission of the DFBK (Figure 1a).…”
Section: Doi: 101002/adom202200417mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, OA is one of the excellent and efficient candidates for regulating excited-state luminescence. [41][42][43][44] Here, we successfully regulated the luminescence of a series of difluoroboron β-diketonate (DFBK) chromophores that were emitted from different electronically excited states at the interface of oleic acid molecules. Selective excitation of OA in the OA-DFBK composites led to blue luminescence, which could be attributed to the locally excited state emission of the DFBK (Figure 1a).…”
Section: Doi: 101002/adom202200417mentioning
confidence: 99%
“…Therefore, OA is one of the excellent and efficient candidates for regulating excited‐state luminescence. [ 41–44 ]…”
Section: Introductionmentioning
confidence: 99%
“…This system can significantly reduce the background signal and improve the detection sensitivity to as low as 24.57 nmol/L. Vafaei et al developed a micellar nanostructure-based DNA sensing system composed of lipid and two nucleic acid probes with a donor and acceptor [ 49 ]. Before the target DNA-binding reaction, two complimentary DNA strands with Cy3 and Cy5 were encapsulated into each two micelle structures.…”
Section: Sensitive Plasmonic Nanobiosensors For Viral Dna Detectionmentioning
confidence: 99%
“…[79] Recently, Mendes et al reported a signal amplification strategy for FRET sensing of DNA via DNA-mediated micelles fusion (Figure 5d). [80] In their approach, the lipid-DNA conjugates modified with FRET pairs are incorporated into micellar scaffolds, and recognition of the target complementary DNA brings the two micelles into close contact, thereby facilitating micelle content mixing and resulting in FRET. They obtained ~20-fold enhancement in the sensitivity compared to the conventional single donor-acceptor design.…”
Section: Biosensingmentioning
confidence: 99%